2019
DOI: 10.1053/j.gastro.2018.11.048
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Human Digestive Diseases With CRISPR-Cas9–Modified Organoids

Abstract: Insights into the stem cell niche have allowed researchers to cultivate adult tissue stem cells as organoids that display structural and phenotypic features of healthy and diseased epithelial tissues. Organoids derived from patients' tissues are used as models of disease and to test drugs. CRISPR-Cas9 technology can be used to genetically engineer organoids for studies of monogenic diseases and cancer. We review the derivation of organoids from human gastrointestinal tissues and how CRISPR-Cas9 technology can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(79 citation statements)
references
References 152 publications
1
78
0
Order By: Relevance
“…The capacity to generate these preclinical models from surgical specimens and biopsies also has great potential to foster personalized medicine approaches to combine the highthroughput drug screening with the molecular assessment of organoid models in order to identify key diagnostic and therapeutic biomarkers that will predict which patients are at a higher risk of progression 49 . Furthermore, based on studies that have shown the ability of CRISPR/Cas9mediated genome editing to modify driver genes in human pancreatic ductal organoids, opportunity exists to replicate the genetic mechanisms leading to pancreatic tumorigenesis [50][51][52] .…”
Section: Discussionmentioning
confidence: 99%
“…The capacity to generate these preclinical models from surgical specimens and biopsies also has great potential to foster personalized medicine approaches to combine the highthroughput drug screening with the molecular assessment of organoid models in order to identify key diagnostic and therapeutic biomarkers that will predict which patients are at a higher risk of progression 49 . Furthermore, based on studies that have shown the ability of CRISPR/Cas9mediated genome editing to modify driver genes in human pancreatic ductal organoids, opportunity exists to replicate the genetic mechanisms leading to pancreatic tumorigenesis [50][51][52] .…”
Section: Discussionmentioning
confidence: 99%
“…in vivo orthotropic imaging, introduction of resistance, target validation, etc. A number of methods have proven useful in delivering gene editing into organoids, electroporation, lentiviral transduction and CRISPR [53][54][55] . Furthermore, genome-wide screens using RNAi-or sgRNA libraries 56 could be powerful tools for discovery of new drug targets.…”
Section: Discussionmentioning
confidence: 99%
“…Complimentary approaches to the discovery process are also necessary given the mouse‐intensive nature of most current strategies and the fact that important human–microbiota interactions may not be modeled in a murine system. For example, primary intestinal organoids represent a particularly useful tool to study human epithelium–microbe interactions for several reasons, including: they can be generated directly from humans (with or without disease‐associated genetic polymorphisms); they can be genetically modified using clustered regularly interspaced short palindromic repeats (CRISPR)/Cas technology; they recapitulate important epithelial cell lineages and physical features of the intestinal tract; and they can be seeded with microbes of interest . Another promising approach is to identify factors like metabolites that can impact a response of interest and work to identify the microbes that are responsible for their production .…”
Section: Of Mice and Menmentioning
confidence: 99%
“…For example, primary intestinal organoids represent a particularly useful tool to study human epithelium-microbe interactions for several reasons, including: they can be generated directly from humans (with or without disease-associated genetic polymorphisms); they can be genetically modified using clustered regularly interspaced short palindromic repeats (CRISPR)/Cas technology; they recapitulate important epithelial cell lineages and physical features of the intestinal tract; and they can be seeded with microbes of interest. 93 Another promising approach is to identify factors like metabolites that can impact a response of interest and work to identify the microbes that are responsible for their production. 94,95 As knowledge of the key mechanisms of host-microbiota interactions are revealed, our accuracy in predicting immunomodulatory activity based on the genomic content of a strain or community should markedly improve.…”
Section: Iga-based Purificationmentioning
confidence: 99%